Circular RNA expression profile of knee condyle in osteoarthritis by illumina HiSeq platform. Issue 10 (20th May 2019) - Xiao, Ke; Xia, Zenan; Feng, Bin; Bian, Yanyan; Fan, Yu; Li, Zeng; Wu, Zhihong; Qiu, Guixing; Weng, Xisheng
Abstract: Osteoarthritis (OA) is the utmost commonly arising joint disease. Knee condyles play an essential role during OA progression. Circular RNA (or circRNA) is a novel kind of RNA, which, unlike the well‐known linear RNA, plays an important regulatory role in OA on the basis of a previous research. In our study, expression of circRNAs in OA knee condyle was measured by illumine sequencing platform. A total of 197 differentially expressed circRNAs, such as hg38_circ_0007474 and hg38_circ_0000118 were identified, and 21 target miRNAs, 2466 source genes and 166 394 circRNA‐miRNA‐mRNA pairs were predicted. Further analysis was applied on three OA‐related circRNAs (hsa_circ_0045714, hsa_circ_0002485, and hsa_circ_0005567). The results were partly verified by previous studies. Further biological research is needed to unfold the possible pathway and therapeutic target of OA. Abstract : Circular RNAs (CircRNAs) are novel noncoding RNAs with different biological functions and pathological implications and have been reported to be closely associated with various diseases, including OA. This article gives insight into the differentially expressed circRNA profile between the mild and the severe damaged human OA cartilage.